Effects of post oxidation of SiO2/Si interfaces in ultrahigh vacuum below 450 °C. (August 2022) - Jahanshah Rad, Zahra; Lehtiö, Juha-Pekka; Chen, Kexun; Mack, Iris; Vähänissi, Ville; Miettinen, Mikko; Punkkinen, Marko; Punkkinen, Risto; Suomalainen, Petri; Hedman, Hannu-Pekka; Kuzmin, Mikhail; Kozlova, Jekaterina; et al.
Abstract: Growing SiO2 layer by wet-chemical oxidation of Si surfaces before growth of another insulating film(s) is a used method to passivate Si interfaces in applications (e.g., solar cell, photodiode) at low temperatures (LT) below 450 °C. We report on potential of LT ultrahigh-vacuum (UHV) treatments combined with the wet-chemical oxidation, by investigating effects of LT-UHV oxidation after the wet-chemical growth of SiO2 and before growing Al2 O3 film on top of SiO2 /Si. This method modifies the SiO2 /Si and is found to (i) decrease defect-level density, (ii) increase negative fixed charge density, and (iii) increase carrier lifetime for Al2 O3 /SiO2 /p-Si, as compared to state-of-the-art SiO2 /p-Si reference interfaces without LT-UHV. X-ray photoelectron spectroscopy shows that the LT-UHV treatment decreases amount of Si +3 oxidized atoms in chemically grown SiO2 and also amount of carbon contamination. In order to pave the way for further tests of LT-UHV in silicon technology, we present a design of simple UHV instrument. The above-described benefits are reproduced for 4-inch silicon wafers by means of the instrument, which is further utilized to make LT-UHV treatments for complementary SiO2 /Si interfaces of the native oxide at silicon diode sidewalls to decrease the reverse bias leakage current of the diodes. Highlights: Low-temperature passivation (<450 °C) of silicon interfaces is studied. Chemically grown SiO2 /Si has been tailored with ultrahigh-vacuum post treatments. Decrease in interface defect density as compared to state-of-the-art reference. Increase in carrier lifetime for p-Si at Al2 O3 /Si interfaces.